(untitled) (Arquivos do Mudi, 2023)
Nicotine is one of the main psychoactive and toxic substances found in tobacco and its exposure during the postnatal period can cause several damages to the health of the child during intrauterine development and in adult life. The aim of this study was to evaluate the effect of maternal postnatal nicotine exposure on cardiac parameters in adult rat offspring. Weight monitoring, echocardiography and organ collections were performed. In conclusion, offspring from mothers exposed to nicotine develops cardiac hypertrophy, further male offspring were more affected.